Pengaruh Jumlah Card Sales Representatives Dan Intensitas Program Promosi Terhadap Volume Penjualan Kartu Kredit Pada PT Bank CIMB Niaga Tbk - Zuhdi, Saefudin; Mursid, Miftahudin Abdul (LPPM Institut Bisnis dan Informatika Kesatuan, 2014)
In a marketing business, deep and well-managed approach should be done continuously with the main goals for products and services can be accepted by the customers and the public.. Promotion as one of the supporting aspects has a very important function and can make a profit between customers and company. The purpose of this study is analyzing the data or informations obtained by focusing on the number of sales person (card sales representative) and the intensity of promotional programs to total unit volume of credit card sales. The intensity of this campaign carried out depends on the trends that exist in the community, and it's own sales targets. Based on the results of research conducted, explaining that there is a very strong relationship between the number of card sales representative and intensity of promotion programs onto unit volume sales. Conclusions are drawn based on the analysis that if F count (10,607) compared to the F table at 3.35 then F count is greater (>) than the F table and marked with a significance value of 0.000. T test and analysis results of the F test showed that all the independent variables affect the volume ofcredit card sales at PT. Bank CIMB Niaga Tbk Keywords : number of card sales representative, intensity of promotion programs, and sales volume